Kinetic Studies on the Reaction between Benzyl/Phenacyl Chloride and N,N-Dimethylaniline in Acetone-Water Mixed Solvents - Nallu, M.; Kanagadurgadevi, G. (Asian Journal of Chemistry, 2010)
Rate constants (k1) for the reaction between benzyl chloride (BC)/phenacyl chloride (PC) and N,N-dimethylaniline (DMA) have been determined conductometrically under pseudo-first-order conditions. Second order rate constants (k2) were evaluated in the usual way. The effect of electron withdrawing —CO— group α-to chlorine is not felt on the values of k2(pc + DMA). The marked effect of acetone-water solvent composition on the rate is known from correlation technique with log k2(BC/PC + DMA) with Grunwald-Winsteins (Y) and Kosowar (Z) of solvent polarity parameters.